Preparation method of microstructure double-layer antireflection film system for solar cell cover plate
By forming a microstructured double-layer urgency film system on the solar cell cover, using nano microsphere template and sol coating technology, the problem of single-layer SiO2 anti-reflection film cannot meet the wide band enhancement, and achieve wide band high transparency Increased rate and cost-effectiveness.
Patent Information
- Application Number
- CN202411120781.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-17
AI Technical Summary
The single-layer SiO2 anti-reflection film of existing solar cell covers cannot meet the demand for photovoltaic cells for efficient wide band enhancement, and the TiO2 sol film has a high refractive index, which cannot meet the requirements of a double-layer composite film system.
Using the preparation method of microstructured double-layer urgency film system, by forming nanopolystyrene or nanoSiO2 microsphere template layer on ultra-white glass, combining TiO2 and SiO2 sol coating, the refractive index is reduced through structural changes and material embedding. The light reflection direction is changed to form a double-layer urgency film system with microstructure.
It achieves the improvement of transmittance in a wide band, meets the demand for efficient penetration of photovoltaic cells, matches the production process of ultra-white photovoltaic glass, reduces production costs, and improves the hardness and protection performance of the film system.
Smart Images

Figure CN119143403A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photovoltaic technology, and in particular, relates to a method for preparing a microstructured double-layer antireflection film system for a solar cell cover. Background Art
[0002] Solar double-glass modules require large optical transmittance to improve the efficiency of battery power generation. Currently, ultra-white SiO 2 Anti-reflection glass is used as a battery cover, which can increase the transmittance of sunlight in the visible light region. However, the thin film anti-reflection at this time is only for the visible light region, and the spectral range is narrow. It has a limited improvement on the performance of the module. In order to achieve the wide-band anti-reflection effect of the spectrum and increase the response range of the battery material to further improve the battery efficiency, a cover glass that can effectively increase the transmittance in a wide spectrum is needed. Double-layer composite anti-reflection film is an ideal choice. For double-layer anti-reflection composite film, the role of its surface material is usually to provide a lower refractive index to meet the multi-layer anti-reflection conditions. Secondly, as the surface layer of the film system, it needs to have a certain hardness to protect the film system. Based on the above two points, the liquid phase chemical method usually uses SiO 2 As the upper layer, for the bottom layer of the composite film system, in addition to meeting the refractive index matching conditions with the upper layer and the substrate, a relatively cheap and simple material system is also required to maintain the production cost. Therefore, TiO 2 Sol coating is mostly used, while TiO 2 Sol-prepared pure TiO 2 Since the refractive index of the thin film is relatively high, it cannot meet the requirements of the double-layer composite film system, so it is necessary to reduce its refractive index by changing the material system or structure. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a microstructured double-layer antireflection film system for a solar cell cover. The present invention adopts a method of structural change to solve the problem of single-layer SiO2 in the photovoltaic cover coating industry. 2 Anti-reflection films cannot meet the technical development needs of photovoltaic cells for wide-band and efficient anti-reflection.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a microstructured double-layer antireflection film system for a solar cell cover comprises the following steps:
[0006] (1) After the ultra-white glass of the production line is cleaned by the cleaning machine, nano polystyrene microspheres or nano SiO 2 Organic solvent emulsion of microspheres;
[0007] (2) The organic solvent spreads rapidly under the surface tension of the water film substrate to form a nano-polystyrene microsphere template layer or nano-SiO 2 Microsphere template layer;
[0008] (3) Complete the paving of nano-polystyrene microsphere template layer or nano-SiO 2 The glass prepared by the microsphere template layer enters the drying machine to dry the water used to clean the substrate and the organic solvent used to prepare the template layer;
[0009] (4) After drying, a dry nano-polystyrene microsphere template layer or nano-SiO 2 The ultra-white glass substrate of the microsphere template layer then enters the sol-gel coating process;
[0010] (5) First, a nano-polystyrene microsphere template layer or a nano-SiO 2 The microsphere template layer was coated on a glass substrate using a roller coating method and TiO 2 Sol preparation of TiO 2 Membrane, chemical liquid phase TiO 2 The sol will enter the gaps of the microsphere template, the sol particles will accumulate into a film, and the film will be solidified by heat treatment;
[0011] (6) Then the second layer of film is prepared by roller coating with nano-SiO 2 Microsphere doped SiO 2 Sol preparation of SiO 2 Film, heat-treated cured film;
[0012] (7) When the coated glass enters the tempering furnace for glass tempering, the bottom layer of nano polystyrene microsphere template or solidified nano SiO 2 The microsphere template completes the final shaping of the prepared film and obtains a double-layer antireflection film product with a microstructure.
[0013] Furthermore, in the step (1), the nano polystyrene microspheres or nano SiO 2 The particle size of the microspheres is 50 to 200 nm.
[0014] Furthermore, the solid content of microspheres in the emulsion of step (1) is 0.1-10%.
[0015] Furthermore, the organic solvent in step (1) is ethanol.
[0016] Furthermore, in the steps (2), (3) and (4), the number of microsphere template layers is from a single layer to ten layers.
[0017] Furthermore, the heat treatment temperature in step (5) and step (6) is 100 to 300°C.
[0018] Furthermore, in step (6), the nano-SiO 2 Microsphere doped SiO 2 Sol is coated with SiO 2 During the preparation of the sol, dispersed nano-SiO 2 Microsphere particles make nano-SiO 2 The microspheres are evenly dispersed on the SiO 2 In the sol system, the system is made to complete the coating.
[0019] Furthermore, in step (6), the nano-SiO 2 The particle size of the microspheres is 50 to 200 nm.
[0020] Furthermore, in step (6), SiO 2 Nano-SiO in sol system 2 The solid content of the microspheres is 0.1-10%.
[0021] The beneficial effects of the present invention are as follows: the production and coating processes of ultra-white photovoltaic glass are matched, a particle template is used to form a microstructure to change the refractive index of the thin film material to meet the anti-reflection requirements of the composite film system, and at the same time, nanoparticles are embedded to change the reflection direction of the incident light to obtain a double-layer anti-reflection film product with a microstructure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described below in conjunction with the accompanying drawings.
[0023] Figure 1 The surface morphology and structure of the bottom film of the product of Example 1;
[0024] Figure 2 The surface morphology and structure of the surface film of the product in Example 1;
[0025] Figure 3 The cross-sectional morphology and structure of the product of Example 1;
[0026] Figure 4 This is the full-band transmittance spectrum of the product in Example 1. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] The specific steps for preparing a microstructured double-layer antireflection film product for a solar cell cover are as follows:
[0030] (1) After the ultra-white glass of the production line is cleaned by the cleaning machine, nano-SiO is immediately added to the surface while keeping the surface moist. 2 Ethanol emulsion of microspheres, SiO 2 The particle size of the microspheres is 100 nm, and the solid content of the microspheres in the emulsion is 2%;
[0031] (2) Ethanol spreads rapidly under the surface tension of the water film substrate to form a single layer of nano-SiO 2 Microsphere template layer;
[0032] (3) Complete the tiling of nano-SiO 2 The glass prepared by the microsphere template layer enters the dryer to dry the water used to clean the substrate and the ethanol used to prepare the template layer;
[0033] (4) After drying, a single-layer nano-SiO 2 The ultra-white glass substrate of the microsphere template layer then enters the sol-gel coating process;
[0034] (5) First, prepare nano-SiO 2 The microsphere template layer was coated on a glass substrate using a roller coating method and TiO 2 Sol preparation of TiO 2 Membrane, chemical liquid phase TiO 2 The sol will enter the gaps of the microsphere template, and the sol particles will accumulate into a film, which will be cured by heat treatment at 200°C.
[0035] (6) Then the second thin film is prepared: on SiO 2 During the preparation of the sol, dispersed nano-SiO 2 Microsphere particles make nano-SiO 2 The microspheres are evenly dispersed on the SiO 2 In the sol system, SiO 2 The particle size of the microspheres is 100 nm. 2 The solid content of the microspheres is 4%. The system is coated by roller coating, and the film is cured by heat treatment at 200°C.
[0036] (7) The coated glass enters the tempering furnace for glass tempering while solidifying SiO 2 The microsphere template completes the final shaping of the prepared film and obtains a double-layer antireflection film product with a microstructure.
[0037] Example 2
[0038] The specific steps for preparing a microstructured double-layer antireflection film product for a solar cell cover are as follows:
[0039] (1) After the ultra-white glass of the production line is cleaned by a cleaning machine, an ethanol emulsion of nano-polystyrene microspheres is immediately added to the surface while keeping the surface moist. The particle size of the polystyrene microspheres is 50 nm, and the solid content of the microspheres in the emulsion is 0.1%;
[0040] (2) Ethanol spreads rapidly under the surface tension of the water film substrate to form a three-layer template layer of nano-polystyrene microspheres;
[0041] (3) The glass on which the nano-polystyrene microsphere template layer is prepared is put into a drying machine to dry the water used to clean the substrate and the ethanol used to prepare the template layer;
[0042] (4) After drying, a dry ultra-white glass substrate prepared with three layers of nano-polystyrene microsphere template layers is obtained, and then enters the sol-gel coating process;
[0043] (5) First, a glass substrate with a nano-polystyrene microsphere template layer was coated with TiO 2 Sol preparation of TiO 2 Membrane, chemical liquid phase TiO 2 The sol will enter the gaps of the microsphere template, and the sol particles will accumulate into a film, which will be cured by heat treatment at 100°C.
[0044] (6) Then the second thin film is prepared: on SiO 2 During the preparation of the sol, dispersed nano-SiO 2 Microsphere particles make nano-SiO 2 The microspheres are evenly dispersed on the SiO 2 In the sol system, SiO 2 The particle size of the microspheres is 50 nm, and the SiO 2 The solid content of the microspheres is 0.1%. The system is coated by roller coating, and the film is cured by heat treatment at 100°C.
[0045] (7) When the coated glass enters the tempering furnace for glass tempering, the bottom layer of nano-polystyrene microsphere template is removed, and the final shaping of the prepared film is completed to obtain a double-layer anti-reflection film product with a microstructure.
[0046] Example 3
[0047] The specific steps for preparing a microstructured double-layer antireflection film product for a solar cell cover are as follows:
[0048] (1) After the ultra-white glass of the production line is cleaned by a cleaning machine, an ethanol emulsion of nano-polystyrene microspheres is immediately added to the surface while keeping the surface moist. The particle size of the polystyrene microspheres is 200 nm, and the solid content of the microspheres in the emulsion is 10%;
[0049] (2) Ethanol spreads rapidly under the surface tension of the water film substrate to form a ten-layer template layer of nano-polystyrene microspheres;
[0050] (3) The glass on which the nano-polystyrene microsphere template layer is prepared is put into a drying machine to dry the water used to clean the substrate and the ethanol used to prepare the template layer;
[0051] (4) After drying, a dry ultra-white glass substrate prepared with ten layers of nano-polystyrene microsphere template layers is obtained, and then enters the sol-gel coating process;
[0052] (5) First, a glass substrate with a nano-polystyrene microsphere template layer was coated with TiO 2 Sol preparation of TiO 2 Membrane, chemical liquid phase TiO 2 The sol will enter the gaps of the microsphere template, and the sol particles will accumulate into a film, which will be cured by heat treatment at 300°C.
[0053] (6) Then the second thin film is prepared: on SiO 2 During the preparation of the sol, dispersed SiO 2 Nano-microsphere particles make SiO 2 Nanospheres are evenly dispersed on SiO 2 In the sol system, SiO 2 The particle size of the microspheres is 200 nm. 2 The solid content of the microspheres is 10%. The coating is completed by the system using a roller coating method, and the film is cured by heat treatment at 300°C.
[0054] (7) The coated glass enters the tempering furnace for glass tempering and the bottom polystyrene microsphere template is removed at the same time, completing the final shaping of the prepared film to obtain a double-layer anti-reflection film product with a microstructure.
[0055] Depend on Figures 1 to 4 It can be seen that the bottom film of the microstructured double-layer anti-reflection film product prepared in Example 1 has a relatively loose porous microstructure, which achieves the purpose of reducing the refractive index by using a single material. The upper layer of the film is embedded with nanoparticles, which can effectively change the direction of the incident light, thereby reducing reflection, so that the microstructured double-layer anti-reflection film exhibits good wide-band high transmittance performance.
[0056] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0057] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a microstructured double-layer antireflection film system for a solar cell cover, characterized in that: The following steps are involved: (1) After the ultra-white glass of the production line is cleaned and the surface is kept moist, an organic solvent emulsion of nano-polystyrene microspheres or nano-SiO2 microspheres is immediately added to the surface; (2) The organic solvent spreads rapidly under the surface tension of the water film substrate to form a nano-polystyrene microsphere template layer or a nano-SiO2 microsphere template layer; (3) the glass prepared by paving the nano-polystyrene microsphere template layer or the nano-SiO2 microsphere template layer enters the drying machine to dry the water and organic solvent; (4) After drying, a dry ultra-white glass substrate prepared with a nano-polystyrene microsphere template layer or a nano-SiO2 microsphere template layer is obtained, and then enters a sol-gel coating process; (5) firstly, a TiO2 film is prepared by using a roll coating method on a glass substrate having a nano-polystyrene microsphere template layer or a nano-SiO2 microsphere template layer, using a TiO2 sol, the TiO2 sol will enter the gaps of the microsphere template, the sol particles will accumulate into a film, and the film will be cured by heat treatment; (6) Then, the second thin film is prepared by using a roller coating method and SiO2 sol doped with nano-SiO2 microspheres to prepare a SiO2 film, and heat treatment is performed to solidify the film; (7) When the coated glass enters the tempering furnace for glass tempering, the bottom layer of nano-polystyrene microsphere template or the solidified nano-SiO2 microsphere template is removed to complete the final shaping of the prepared film, thereby obtaining a double-layer antireflection film product with a microstructure.
2. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The particle size of the nano polystyrene microspheres or nano SiO2 microspheres in step (1) is 50 to 200 nm.
3. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The solid content of microspheres in the emulsion of step (1) is 0.1-10%.
4. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The organic solvent in step (1) is ethanol.
5. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The number of microsphere template layers in step (2), step (3) and step (4) is from a single layer to ten layers.
6. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The heat treatment temperature in step (5) and step (6) is 100 to 300°C.
7. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The SiO2 sol doped with nano-SiO2 microspheres in step (6) is prepared by doping and adding dispersed nano-SiO2 microsphere particles during the preparation of the coating SiO2 sol.
8. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The particle size of the nano-SiO2 microspheres in step (6) is 50 to 200 nm.
9. The method for preparing a microstructured double-layer antireflection film system for a solar cell cover according to claim 1, characterized in that: The solid content of nano-SiO2 microspheres in the SiO2 sol system in step (6) is 0.1-10%.
Citation Information
Patent Citations
Preparation method of composite ordered porous nanometer titanium dioxide (TiO2) film
CN102486967A
Preparation method for antireflection film of solar cell
CN103022252A
A method of constructing a super-hydrophilic anti-reflection damp-proof composite film on a glass substrate
CN105731821A
Method for preparing high strength double-layer anti-reflection film
CN105789340A
Preparation method of antireflection coating liquid for double-layer coating
CN114196321A
